Tympanic Membrane Retraction Pocket Overview and Advances in Diagnosis and Management - Mansour, Salah; Magnan, Jacques; Haidar, Hassan; Nicolas, Karen (Springer International Publishing : Imprint: Springer, 2015)
This book reviews current knowledge of the etiopathogenesis, pathophysiology, and molecular biology of tympanic membrane retraction pockets and provides clear guidance on clinical assessment and treatment. A new diagnostic approach based on clinicoradiologic correlations is presented, and the ability of computer tomography to offer objective criteria for improved differentiation between stable and unstable or unsafe retraction pockets is explained. Surgical options are discussed, and on the basis of their own clinical and surgical experiences the authors propose a novel procedure, masto-atticotomy with anterior epitympanotomy (AER surgery), which addresses the causative factors underlying a retraction pocket. This surgery aims to restore adequate aeration routes for the middle ear compartments situated above the tympanic diaphragm; it results in better control of the pathology and in most cases prevents its recurrence. The book will assist otologists and surgeons in ensuring that retraction pockets are effectively diagnosed and treated, avoiding progression to cholesteatoma.